Alternative Bedding Materials to Improve Growth Performance and Welfare of Broilers - Boussaada , Tarek; Ouachem, Derradji (International Journal of Poultry Science, 2019)
Objective: The aim of this study was to evaluate the effects of five litter types on the growth performance and some welfare indicators (pododermatitis, hock burns, breast blister and feather cleanliness) in broilers over rearing cycle of 42 days. Materials and Methods: The used litter types were wood shaving, sawdust, standard quality straw, low quality straw and crop residues. A total of six hundred one day-old male broilers (Cobb 700) were randomly allocated to 5 treatments with 6 replicates of 20 chicks each. Results: Results showed that at the age of 7 day, the FCR and body weight were significantly improved (-5%, p = 0.002; +9,5%, p = 0.015 respectively) in broilers reared on sawdust. Furthermore, the heavier BW observed in broiler reared on sawdust at an early age persist at the slaughter age (+4.95%; p = 0.01). In contrast, low quality straw resulted in lower (p = 0.01) final body weight and feed conversion ratio. On the other hand, pododermatitis lesions appear from the first week in all litter types. The rate of severity of foot pad dermatitis increased significantly with the age of the birds (p0.05). Conclusion: It is concluded that the birds reared on sawdust showed the best BW and FCR. However, broilers kept on wood shaving had the best score of plumage and hock burn. The presence of scratches was not observed in any treatment.